التحولات العمرانية في مدينة طبرق خلال الفترة (2005 – 2025 م) دراسة جغرافية واستشراق حضري حتى عام 2035 م - جودة, أميرة أحمد عثمان (Al-Qurtas, 2026)
التحولات العمرانية في مدينة طبرق خلال الفترة (2005 – 2025 م) دراسة جغرافية واستشراق حضري حتى عام 2035 م